The market, macroeconomic, and behavioural factors in emerging markets: the case of Poland - Schabek, Tomasz; Barros, Lucas Ayres Barreira de Campos (Publishing House of Wroclaw University of Economics and Business, 2021)
The study tests a broad set of market, macroeconomic, and behavioural factors in the Polish stock market using local and US data. In time series regressions, employing general-to-specific modelling and principal component analysis, the authors found that both local and foreign aggregate indicators significantly predict the behaviour of a broad portfolio of Polish stocks. However, no common factor is able to explain the cross-section of expected returns in Poland. Only firm-specific characteristics, in particular market/book value and momentum, show significance in the cross-sectional analysis. The results are consistent with recent methodological critiques, suggesting that most candidate factors fail to explain the cross-section of expected returns when more stringent inference procedures are adopted
Argumenta Oeconomica, 2021, Nr 1 (46), s. 131-154